(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the integration of technology, and specifically Computer-Assisted Language Learning (CALL) tools, into English as a Foreign Language (EFL) classrooms, with a focus on its effect on learner engagement and linguistic proficiency. Employing a quasi-experimental design, the study compared two groups of intermediate EFL learners over a ten-week instructional period: one taught through a technology-integrated syllabus incorporating multimedia resources, mobile-assisted language-learning applications, and online collaborative platforms, and another instructed through conventional textbook-based methods. Data were gathered through pre- and post-tests measuring vocabulary retention and speaking fluency, supplemented by a learner engagement questionnaire administered at the close of the study. Findings indicate that the technology-integrated group demonstrated measurably higher gains in both vocabulary retention and oral fluency, alongside elevated self-reported engagement and motivation, when compared with the control group. These results substantiate the pedagogical value of deliberately and purposefully integrated technology, suggesting that CALL tools, when aligned with clear instructional objectives rather than deployed for novelty alone, can meaningfully enhance both linguistic outcomes and classroom dynamics. Implications for curriculum design and teacher training are discussed, alongside limitations that warrant a cautious interpretation of the findings.